2020
DOI: 10.1038/s41598-020-72827-5
|View full text |Cite
|
Sign up to set email alerts
|

A randomised trial evaluating the effect of intraoperative iron administration

Abstract: Perioperative anaemia increases postoperative morbidity and mortality, and iron deficiency is anaemia’s most common cause in surgical patients. Preoperative intravenous iron increases postoperative haemoglobin; however, data regarding intraoperative intravenous iron’s effectiveness are inadequate. This study examined intraoperative intravenous iron’s effects on postoperative haemoglobin levels in adults. Fifty-seven healthy subjects (aged 19–40 years) scheduled for bimaxillary orthognathic surgery were assigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…ferric derisomaltose after anaesthetic induction resulted in higher Hb levels and a significant increase in reticulocyte production index at 2 weeks postoperatively compared with placebo. 1022 This supports the results of an earlier study, which demonstrated that peri-operative i.v. iron isomaltoside infusion (1000 mg) resulted in significantly increased Hb levels and a lower incidence of anaemia in cardiac surgery patients at 1 month after surgery.…”
Section: Evidence Summarysupporting
confidence: 91%
“…ferric derisomaltose after anaesthetic induction resulted in higher Hb levels and a significant increase in reticulocyte production index at 2 weeks postoperatively compared with placebo. 1022 This supports the results of an earlier study, which demonstrated that peri-operative i.v. iron isomaltoside infusion (1000 mg) resulted in significantly increased Hb levels and a lower incidence of anaemia in cardiac surgery patients at 1 month after surgery.…”
Section: Evidence Summarysupporting
confidence: 91%
“…Finally, we did not measure the long-term postoperative changes in hemoglobin, iron, and ferritin levels, such as those occurring over weeks to months. However, based on previously reported findings [ 30 , 43 ], sufficient amounts of iron and ferritin in patients with IV iron therapy may play roles in restoring appropriate hemoglobin levels postoperatively. However, our study is the first to perform a non-inferiority comparison of the effect of a novel IV iron drug (ferric carboxymaltose) and conventional blood salvage therapy (autologous whole blood donation) on the postoperative hemoglobin level in robust young patients undergoing bimaxillary orthognathic surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we did not measure the long-term postoperative changes in hemoglobin, iron, and ferritin levels, such as those occurring over weeks to months. However, based on previously reported ndings [30,43], su cient amounts of iron and ferritin in patients with IV iron therapy may play roles in restoring appropriate hemoglobin levels postoperatively.…”
Section: Discussionmentioning
confidence: 99%